Ceramic implants (Y‐TZP): are they a viable alternative to titanium implants for the support of overdentures? A randomized clinical trial. Issue 12 (10th October 2013) - Osman, Reham B.; Swain, Michael V.; Atieh, Momen; Ma, Sunyoung; Duncan, Warwick
Abstract Objective The objective of this study was to assess 1‐year clinical success of one‐piece zirconia implants compared with similar‐design titanium implants, in the context of a novel protocol for implant distribution. Materials and Methods Twenty‐four edentulous participants were randomly allocated to one‐piece titanium or zirconia implant group. Each participant received four implants in the maxilla (mid‐palatal and three anterior crestal implants) and three implants in the mandible (mid‐symphyseal and two bilateral distal implants). Conventional loading protocol was followed. Marginal bone remodeling and clinical success of implants were evaluated. The data were statistically analyzed, and risk predictors for implant failures were evaluated. Results There was no significant difference in the survival rate between the two groups. In the mandible, the survival rate of titanium implants was 95.8% vs. 90.9% for the zirconia implants. The corresponding values in the maxilla were 71.9% and 55%, respectively. Three implants in the zirconia group fractured. Statistically significant less marginal bone loss was observed around titanium implants (0.18 mm) compared with the zirconia group (0.42 mm). The prediction model revealed a higher risk for implant failures in the maxilla (P < 0.0001). Conclusion The outcome of this study indicates caution before recommendation can be made for the use of single‐piece zirconia implants for overdenture support. Their use should be limited to cases with proven allergy to titanium. This is mainly due to the increased bone loss and higher fracture rate observed for zirconia implants. Future biomaterial research should focus on producing surface characteristics on zirconia implants with outcomes similar to those established for the optimum osseointegration of titanium implants.